Macroeconomic Developments and Prospects in Low-Income Developing Countries : 2015. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This paper examines macroeconomic developments and prospects in low-income developing countries (LIDCs) against the back-drop of a sharp fall in international commodity prices. The focus here-by contrast with IMF (2014a)-is on recent developments and the near-term outlook, recognizing that the new price environment is likely to remain in place for several years to come. The paper also includes a section examining the experience of LIDCs with capital inflows over the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet